THE TRIBAL AND CHRISTIAN PARADIGMS IN THE INTERPRETATION OF EPIC HEROES - Голозубов, А. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The paper considers the interaction of pagan and Christian paradigms on the example of the Icelandic tribal society’s military ethic and narrative model of the Anglo-Saxon heroic epic poems.